OIL AND SATURATED/UNSATURATED FATS GATHERING IN THE PATH OF CORIANDER (CORIANDRUM SATIVUM L.) FRUIT RIPENING BENEATH NATURAL CULTIVATION - Shroff, Prof. Ahmad; Aiyar , Prof. Subhash; Khan , Prof. Aiysha (International Journal of Multidisciplinary Research and Studies, 2021)
To examine the buildup of oil and fatty acids in coriander for the duration of fruit ripening, an area test become performed below natural cultivation situations in Such (close to Toulouse, southwestern France) for the duration of the 2009 cropping season. The percent and composition of the fatty acids of coriander had been decided with the aid of using fuel line chromatography. Our outcomes confirmed that fast oil accumulation began out in early stages (2 days after flowering, DAF). Twelve fatty acids had been identified. Saturated and polyunsaturated acids had been the dominant fatty acids at in advance stages (2–12 DAF), however, reduced after this date. After this stage, petroselinic acid multiplied to its maximum quantity at 18 DAF. In contrast, palmitic acid observed the alternative trend. Saturated and polyunsaturated fatty acids reduced markedly and monounsaturated fatty acids multiplied for the duration of fruit maturation. It seems that the fruit of coriander can be harvested earlier than complete maturity.[19]